The ABC of funerals. Humour and satire on funerary rituals in contemporary Japan - Chiara Ghidini (Between, 2017)
In the 1960s Tamamuro Taijō, observing how funerals had become the main activity of Japanese Buddhism, critically coined the expression “Funeral Buddhism” to refer to Buddhist practices in modern Japan. Later developments led to an increasing process of commodification, in some cases even spectacularisation, of funeral rituals, applied also to real and robotic pets, as well as to people who are still alive. This commodification has been acknowledged and analysed in a humoristic and/or satirical key within contemporary Japanese fiction and cinema. In particular, the article aims to focus on a story written by Matsuura Rieko, entitled The Day of the Funeral (1978), and on the film The Funeral (1984), by internationally acclaimed director Itami Jūzō.